Research handbook on civil-military relations - Croissant, Aurel; Kühn, David; Pion-Berlin, David (Edward Elgar Publishing Limited, 2024)
Bringing together leading scholars from across the world, this comprehensive Research Handbook analyses key problems, subjects, regions, and countries in civil-military relations. Showcasing cutting-edge research developments, it illustrates the deeply complex nature of the field and analyses important topics in need of renewed consideration.
Gesehen am 01.08.2024
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Sicherheitspolitik; Zivil-militärische Zusammenarbeit